Curriculum for training in peroral endoscopic myotomy (POEM) in Europe (Part I): European Society of Gastrointestinal Endoscopy (ESGE) Position Statement - Rodríguez de Santiago, Enrique; Tate, David J.; Santos-Antunes, João; Nagl, Sandra; Vacková, Zuzana; Tantau, Marcel; Araujo, Isis K.; de Moura, Eduardo Guimarães Hourneaux; Familiari, Pietro; Messmann, Helmut; Ebigbo, Alanna; Fockens, Paul; Bisschops, Raf; Heinrich, Henriette; Albéniz, Eduardo; Sethi, Amrita; Kiosov, Oleksandr; Martinek, Jan; Soetikno, Roy; Gralnek, Ian M.; Tham, Tony C. (Endoscopy, 2025)
Peroral endoscopic myotomy (POEM) is an advanced endoscopic procedure that has become a first-line treatment for esophageal achalasia and other esophageal spastic disorders. Structured training is essential to optimize the outcomes of this technique. The European Society of Gastrointestinal Endoscopy (ESGE) has recognized the need to formalize and enhance training in POEM. This Position Statement presents the results of a systematic review of the literature and a formal Delphi process, providing recommendations for an optimal training program in POEM that aims to produce endoscopists competent in this procedure. In a separate document (POEM curriculum Part II), we provide technical guidance on how to perform the POEM procedure based on the best available evidence.1 POEM trainees should acquire a comprehensive theoretical knowledge of achalasia and other esophageal motility disorders that encompasses pathophysiology, diagnostic tool proficiency, clinical outcome assessment, potential adverse events, and periprocedural management.2 Experience in advanced endoscopic procedures (endoscopic mucosal resection and/or endoscopic submucosal dissection [ESD]) is encouraged as a beneficial prerequisite for POEM training.3 ESGE suggests that POEM trainees without ESD experience should perform an indicative minimum number of 20 cases on ex vivo or animal models before advancing to human POEM cases with an experienced trainer.4 ESGE recommends that the trainee should observe an indicative minimum number of 20 live cases at expert centers before starting to perform POEM in humans.5 The trainee should undertake an indicative minimum number of 10 cases under expert supervision for the initial human POEM procedures, ensuring that trainees can complete all POEM steps independently.6 ESGE recommends avoiding complex POEM cases during the early training phase. 7 POEM competence should reflect the technical success rate, both the short- and long-term clinical success rates, and the rate of true adverse events.8 A POEM center should maintain a prospective registry of all procedures performed, including patient work-up and outcomes, procedural techniques, and adverse events.